Coral Reef Degradation Differentially Alters Feeding Ecology of Co-occurring Congeneric Spiny Lobsters - Briones-Fourzán, Patricia; Álvarez-Filip, Lorenzo; Barradas-Ortíz, Cecilia; Morillo-Velarde, Piedad S.; Negrete-Soto, Fernando; Segura-García, Iris; Sánchez-González, Alberto; Lozano-Álvarez, Enrique (Frontiers in Marine Science, 2019)
Caribbean coral reefs are undergoing massive degradation, with local increases of macroalgae and reduction of architectural complexity associated with loss of reef-building corals. We explored whether reef degradation affects the feeding ecology of two co-occurring spiny lobsters: Panulirus guttatus, which is an obligate reef-dweller, and Panulirus argus, which uses various benthic habitats including coral reefs. We collected lobsters of both species from the back-reef zones of two large reefs similar in length ( 1.5 km) but differing widely in level of degradation, at the Puerto Morelos Reef National Park (Mexico). We measured the carapace length (CL) and weight (W) of lobsters, estimated three condition indices (hepatosomatic index, HI; blood refractive index, BRI; and W/CL ratio), and analyzed their stomach contents and stable isotope values (15N and 13C). All lobsters tested negative for the presence of the virus PaV1, which can affect nutritional condition. Stomach contents yielded 72 animal taxa, mainly mollusks and crustaceans, with an average of 35 taxa per species per reef, but with much overlap. In P. guttatus, CL, HI, BRI, and W/CL did not vary with reef, but mean isotopic values did. The isotopic niche of P. guttatus showed little overlap between reefs, reflecting differences in local carbon sources and underlining the habitat specialization of P. guttatus, which exhibited a higher trophic position on the more degraded reef. Overall, the trophic position of P. guttatus was higher than that of P. argus. In P. argus, none of the variables differed between reefs and the isotopic niche was wide and with great overlap between reefs, reflecting the broader foraging ranges of P. argus compared to P. guttatus. Additional isotopic values from 16 P. argus caught at a depth of 25 m in the fore reef suggest that these larger lobsters forage over different habitats and have a higher trophic position than their smaller conspecifics and congeners from the back reef. The feeding ecology of P. argus appears to be less influenced by coral reef degradation than that of P. guttatus, but our results suggest a buffering effect of omnivory against habitat degradation for both lobster species.